State-of-the-Art Materials Used in MEMS Micromirror Arrays for Photonic Applications - Liu, Shujie; Kästner, Philipp; Donatiello, Roland; Shrivastava, Anup; Smolarczyk, Marek; Iskhandar, Mustaqim Siddi Que; Hasan, Md Kamrul; Caruso, Giuseppe; Chen, Jiahao; Elsaka, Basma; Baby, Shilby; Löber, Dennis; et al. (Photonics, 2024)
This work provides an overview on micromirror arrays based on different material systems such as dielectrics, element silicon, compound semiconductors, metals, and novel 2D materials. The goal is to work out the particular strength of each material system to enable optimum performance for various applications. In particular, this review is intended to draw attention to the fact that MEMS micro-mirrors can be successful in many other material systems besides silicon. In particular, the review is intended to draw attention to two material systems that have so far been used less for MEMS micromirror arrays, that have been less researched, and of which fewer applications have been reported to date: metallic heterostructures and 2D materials. However, the main focus is on metallic MEMS micromirror arrays on glass substrates for applications like personalized light steering in buildings via active windows, energy management, active laser safety goggles, interference microscopy, and endoscopy. Finally, the different micromirror arrays are compared with respect to fabrication challenges, switching speed, number of mirrors, mirror dimensions, array sizes, miniaturization potential for individual mirrors, reliability, lifetime, and hinge methodology.
CRIS-Team Scopus Importer:2024-04-19
Keywords: 2D materials; dielectric mirrors; light steering; metallic mirrors; miniaturization potential; safety; semiconductor mirrors; sensorics; smart glass; spectroscopy; wavelength tuning